Preparation method of poly (vinylidene fluoride-trifluoroethylene) electrostatic spinning piezoelectric film
By induced the orientation and defect of the sheet crystal by using the tensile force field during electrospinning, and combined with annealing treatment to promote the generation of orientation amorphous components, the problem of difficult to increase the piezoelectric coefficient in pure polymer systems is solved, and high Preparation of electrospinned piezoelectric film with piezoelectric properties.
Patent Information
- Application Number
- CN202411847829.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art is difficult to significantly improve the piezoelectric coefficient in pure polymer systems, and the introduction of nanofillers will damage the flexibility and mechanical properties of the polymer.
By induced crystal orientation and defectization by using tensile force field during electrospinning, and combined with annealing treatment, the formation of oriented amorphous components with different contents in restricted wafers is established, and annealing temperature field and orientation amorphous structure are established. The relationship between piezoelectric properties.
The piezoelectric coefficient of poly(vinylidene fluoride-trifluoroethylene) was significantly improved, and an electrospinned piezoelectric film with high voltage electrical properties was prepared.
Smart Images

Figure CN119392448A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ferroelectric polymers, in particular to a method for preparing a poly(vinylidene fluoride-trifluoroethylene) electrostatic spinning piezoelectric film. Background Art
[0002] PVDF is a semi-crystalline polymer. Due to the flexibility of the chain, it has five different crystal phases, namely α, β, γ, δ and ε. α and ε phases are non-polar phases, while β, γ and δ phases are ferroelectric polar phases. These different crystal phases share three different conformations, namely cis-trans alternating (TGTG) conformation, all-trans (TTTT) conformation and intermediate conformation (T3GT3G). Among them, the β crystal phase with TTTT conformation is considered to be the most ideal crystal phase for piezoelectricity, because all fluorine atoms are located on the same side of the carbon chain, which helps to improve the polarity. A large number of studies have shown that in order to improve the piezoelectric coefficient of PVDF-based materials, it is necessary to increase its dielectric constant and β crystal content. To achieve this goal, the most common and effective method is to add nanofillers such as barium titanate (BaTiO3), zinc oxide (ZnO) and graphene oxide to PVDF-based materials. However, the introduction of a large number of fillers is prone to agglomeration, which will also damage the flexibility of the polymer and cause mechanical mismatch of the material, which will greatly affect the physical properties of the material. To solve these problems, the piezoelectric properties of pure polymer systems need to be studied.
[0003] In the prior art, in order to improve the piezoelectric properties of materials, researchers usually adjust the molecular conformation of polyvinylidene fluoride-based materials. However, unlike polymer / filler composite systems, it is very difficult to achieve a significant increase in the piezoelectric coefficient of a pure polymer system. Our recent research has found that inducing the formation of oriented amorphous components at the interface between the crystalline region and the amorphous region can significantly improve the piezoelectric coefficient. Studies have reported that the content of oriented amorphous components is affected by the external processing field parameters. For example, regulating the temperature field parameters during annealing can change the crystallinity of nylon 6 and thus affect the oriented amorphous content. However, with different polymer structures, the corresponding response rules are not necessarily the same, which has brought troubles to research aimed at improving the piezoelectricity of piezoelectric materials. Summary of the invention
[0004] In order to address the deficiencies in the prior art, the present application takes highly polar poly(vinylidene fluoride-trifluoroethylene) as the research object, utilizes the stretching force field in the electrospinning process to induce the orientation and defect formation of the lamellae, and cooperates with the subsequent annealing treatment to promote the generation of oriented amorphous components of different contents in the confined wafer, establishes the relationship between the annealing temperature field and the content of the oriented amorphous components, and the relationship between the annealing temperature field and the piezoelectric properties, so as to significantly improve the piezoelectric coefficient of poly(vinylidene fluoride-trifluoroethylene).
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a poly (vinylidene fluoride-trifluoroethylene) electrospun piezoelectric film, and its preparation method comprises the following steps:
[0007] Adding poly(vinylidene fluoride-trifluoroethylene) into the mixed solvent and stirring continuously to obtain a uniform electrospinning solution;
[0008] Add the prepared electrospinning solution into the syringe and perform spinning at a certain feeding speed. Adjust the spinning parameters and environmental parameters before performing spinning to obtain a piezoelectric fiber membrane;
[0009] The obtained fiber membrane was completely dried in a blast oven and then post-processed, and then placed in a crucible and annealed at different temperatures using a muffle furnace to obtain multiple groups of annealed samples;
[0010] The molar percentage of vinylidene fluoride and trifluoroethylene in the poly(vinylidene fluoride-trifluoroethylene) is 80 / 20%.
[0011] In some possible implementations, the poly(vinylidene fluoride-trifluoroethylene) electrospinning piezoelectric film is characterized in that the annealing temperature is 120-140°C.
[0012] The preferred annealing temperatures are 120, 125, 130, 135, and 140° C., respectively.
[0013] In some possible implementations, the poly(vinylidene fluoride-trifluoroethylene) electrospinning piezoelectric film is characterized in that the weight average molecular weight of the poly(vinylidene fluoride-trifluoroethylene) is 450,000 g / mol.
[0014] In some possible implementations, the poly(vinylidene fluoride-trifluoroethylene) electrospun piezoelectric film is characterized in that the post-treatment process is: placing the dried film in a 120×120cm crucible and using a muffle furnace to anneal the poly(vinylidene fluoride-trifluoroethylene) electrospun piezoelectric film at different temperatures (120-140°C).
[0015] In some possible implementations, the drying process is air-blast drying, and the temperature of the air-blast drying is 55°C.
[0016] In some possible implementations, the electrospinning equipment parameters of the prepared poly(vinylidene fluoride-trifluoroethylene) electrospinning piezoelectric film are set to: feed rate 1.0 ml / h, external electric field 16 kilovolts, distance from needle tip to collector 12 cm, drum speed 1500 rpm: the environmental parameters are set to: 25°C and relative humidity 40-50%.
[0017] In some possible implementations, the volume ratio of N,N-dimethylformamide to acetone in the mixed solvent is 3:2.
[0018] In some possible implementations, the purity of each component in the mixed solvent is greater than 99.9%.
[0019] The present application also provides a poly(vinylidene fluoride-trifluoroethylene) electrospinning piezoelectric film prepared by the above preparation method.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The invention takes highly polar poly (vinylidene fluoride-trifluoroethylene) as a research object, utilizes the tensile force field produced under the electrostatic spinning preparation process to induce the orientation and defect of the lamellae, cooperates with the later annealing treatment to promote the generation of oriented amorphous components with different contents in the restricted wafer, establishes the relationship between the annealing temperature field and the oriented amorphous structure, and the structure and the piezoelectric performance, so that the piezoelectric coefficient of poly (vinylidene fluoride-trifluoroethylene) is greatly improved, and the obtained poly (vinylidene fluoride-trifluoroethylene) based polymer piezoelectric film is prepared, and poly (vinylidene fluoride-trifluoroethylene) is used as a raw material for electrostatic spinning, and the annealing temperature during the post-treatment is controlled to prepare the poly (vinylidene fluoride-trifluoroethylene) electrostatic spinning piezoelectric film with high piezoelectric performance. The electrostatic spinning piezoelectric film takes poly (vinylidene fluoride-trifluoroethylene) as the object, and induces the orientation and defect of the lamellae through the tensile force field produced under the electrostatic spinning technology process, cooperates with the later annealing treatment to promote the generation of oriented amorphous regions with different structures in the restricted lamellae, and obtains the electrostatic spinning piezoelectric film with high piezoelectric performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The performance of the poly (vinylidene fluoride - trifluoroethylene) electrospun piezoelectric film in Examples 1-5 and Comparative Example 1 of the present invention and the content of the crystalline region, amorphous region, and oriented amorphous region (X C , X OFA , X IFA ) comparison chart. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The present invention provides a poly(vinylidene fluoride-trifluoroethylene) electrospun piezoelectric film, wherein the content of oriented amorphous components in the poly(vinylidene fluoride-trifluoroethylene) film is regulated by annealing; after annealing, the content of oriented amorphous regions in the piezoelectric film is greatly increased; the increase in the content of oriented amorphous regions increases the residual polarization strength, and the preparation method thereof is as follows:
[0025] Adding poly(vinylidene fluoride-trifluoroethylene) into the mixed solvent and stirring continuously to obtain a uniform electrospinning solution;
[0026] Add the prepared electrospinning solution into the syringe and perform spinning at a certain feeding speed. Adjust the spinning parameters and environmental parameters before performing spinning to obtain a piezoelectric fiber membrane;
[0027] The obtained fiber membrane was completely dried in a blast oven and then post-processed, and then placed in a crucible and annealed at different temperatures using a muffle furnace to obtain multiple groups of annealed samples;
[0028] The molar percentage of vinylidene fluoride and trifluoroethylene in the poly(vinylidene fluoride-trifluoroethylene) is 80 / 20%.
[0029] This application takes poly(vinylidene fluoride-trifluoroethylene) 80 / 20 with a fully polar TTTT conformation as the research object, utilizes its high residual polarization strength and combines the tensile force field generated by the electrospinning preparation process to induce the orientation and defect formation of the lamellae, and cooperates with annealing treatment to promote the formation of oriented amorphous components in the confined chip, effectively promoting the growth of oriented amorphous structure to improve the piezoelectric performance.
[0030] Among them, annealing induces the growth of oriented amorphous components in poly(vinylidene fluoride-trifluoroethylene) film. The large amount of oriented amorphous components and high residual polarization intensity make its longitudinal piezoelectric coefficient much higher than that of poly(vinylidene fluoride-trifluoroethylene) film that has not been annealed.
[0031] In some embodiments, the annealing temperatures of the poly(vinylidene fluoride-trifluoroethylene) electrospun piezoelectric films are 120, 125, 130, 135, and 140° C., respectively.
[0032] Preferably, the annealing temperature of the poly(vinylidene fluoride-trifluoroethylene) electrospinning piezoelectric film is 130°C.
[0033] When the annealing temperature of poly(vinylidene fluoride-trifluoroethylene) electrospun piezoelectric film is 130℃, the induced amorphous content is 0.4, the longitudinal piezoelectric coefficient d 33 It can reach 42.4 picometers per volt. After it is prepared into an energy harvester, the peak voltage can reach 793 millivolts under a mechanical force of 37.5 Newtons.
[0034] In some embodiments, the weight average molecular weight of poly(vinylidene fluoride-trifluoroethylene) is 450,000 g / mol.
[0035] In the present application, electrospinning of highly polar poly(vinylidene fluoride-trifluoroethylene) 80 / 20 is performed, and annealing treatment is performed to significantly increase the piezoelectric coefficient of the poly(vinylidene fluoride-trifluoroethylene).
[0036] The drying process includes air blast drying, and the temperature of the air blast drying is 55°C.
[0037] In some embodiments, the solvent is a mixed solvent of N,N-dimethylformamide (DMF) and acetone in a volume ratio of 3:2.
[0038] The present application also provides a method for preparing the poly(vinylidene fluoride-trifluoroethylene) electrospinning piezoelectric film.
[0039] The scheme of the present invention will be explained below in conjunction with specific examples and comparative examples. Those skilled in the art will understand that the following examples are only used to explain the present invention and cannot be understood as limiting the present invention. Among them, the poly (vinylidene fluoride-trifluoroethylene) used was purchased from Arkema, and other reagents, software and instruments involved that are not specifically explained are all conventional commercial products or open source.
[0040] Example 1
[0041] A poly(vinylidene fluoride-trifluoroethylene) electrospinning piezoelectric film, the preparation of which comprises the following steps:
[0042] (1) Preparation of electrospinning solution: Dissolve poly(vinylidene fluoride-trifluoroethylene) 80 / 20 powder in a mixed solvent of N,N-dimethylformamide (DMF) and acetone in a volume ratio of 3:2, and stir to obtain an electrospinning solution. The weight average molecular weight of the poly(vinylidene fluoride-trifluoroethylene) is 450,000 g / mol, and the stirring time is 12 hours.
[0043] (2) Preparation of piezoelectric film: The uniformly mixed electrospinning solution in (1) was added to a standard syringe, and the spinning was carried out at a feed rate of 1 ml / h, an external electric field of 16 kV, a distance from the needle tip to the collector of 12 cm, a drum speed of 1500 rpm, an ambient temperature of 25°C, and an ambient relative humidity of 40-50%. The obtained piezoelectric fiber membrane was completely dried in a 55°C forced air oven and then annealed at 130°C to obtain a poly(vinylidene fluoride-trifluoroethylene) electrospun piezoelectric film (EFC20-A130).
[0044] Example 2
[0045] The difference between Example 2 and Example 1 is that the annealing temperature in step (2) is 120° C. (EFC20-A120).
[0046] Example 3
[0047] The difference between Example 3 and Example 1 is that the annealing temperature in step (2) is 125°C (EFC20-A125).
[0048] Example 4
[0049] The difference between Example 4 and Example 1 is that the annealing temperature in step (2) is 135°C (EFC20-A135).
[0050] Example 5
[0051] The difference between Example 5 and Example 1 is that the annealing temperature in step (2) is 140° C. (EFC20-A140).
[0052] Comparative Example 1
[0053] The difference between Comparative Example 1 and Example 1 is that the piezoelectric fiber membrane after drying in step (2) is not annealed (EFC20-A0).
[0054] The dielectric constants (ε) of the poly(vinylidene fluoride-trifluoroethylene) electrospun piezoelectric films prepared in Examples 1-5 and Comparative Example 1 r '), residual polarization intensity (P r ), crystalline area, amorphous area, oriented amorphous area content (X C , X OFA , X IFA ) The specific test method is as follows:
[0055] (1) Dielectric constant: Before measurement, a plasma magnetic sputtering coating apparatus was used to construct gold electrodes with an area of 28.26 square millimeters on both surfaces of the poly(vinylidene fluoride-trifluoroethylene) electrospun piezoelectric film sample to form electrodes with a diameter of 6 millimeters. A 1.0 volt root voltage was applied. The data obtained at the same frequency at room temperature (25°C) were plotted into a data graph for comparison.
[0056] (2) Residual polarization intensity: The polarization-electric field (PE) loop test is performed using a ferroelectric tester combined with a high-voltage amplifier. Gold electrodes are sputtered on both sides of the above-mentioned film sample, with an overlapping area of 0.07069 square centimeters. The gold-plated film is immersed in silicone oil to avoid corona discharge in the air. A voltage with a bipolar or unipolar sinusoidal waveform is applied at 10 Hz. The residual polarization intensity data obtained from the PE cycle test of several groups of samples are plotted into a data graph for comparison.
[0057] (3) One-dimensional wide-angle X-ray diffraction (1D-WAXD) analysis: Place the sample on the sample stage, select the transmission mode, the incident wavelength is 0.154184 nm, the distance between the sample and WAXD is 6 mm, and the scanning q value range is 5-34 nm -1 .
[0058] The performance test results of the poly(vinylidene fluoride-trifluoroethylene) electrospun piezoelectric films prepared in Examples 1-5 and Comparative Example 1 are as follows: Figure 1 shown.
[0059] Figure 1 The properties of poly(vinylidene fluoride-trifluoroethylene) electrospun piezoelectric films in Examples 1-5 and Comparative Example 1 and the contents of crystalline region, amorphous region, and oriented amorphous region (X C , X OFA , X IFA )contrast.
[0060] Combination Figure 1 , the analysis is as follows:
[0061] (1) The highest dielectric constant (3.02) is obtained when the annealing temperature is 130°C. However, due to the porous structure morphology inside the electrospun film, larger defects are caused, making it impossible to continue to apply a larger electric field.
[0062] (2) Due to the reasons mentioned in (1), the residual polarization of the film was compared under a low electric field (60 mV / m), and it was found that the polarization intensity showed a trend of gradual increase with the increase of annealing temperature. The residual polarization intensity of the film annealed at 140°C was the highest (0.35 mCoulomb / m2). The residual polarization and the crystallization of the β crystal are both related to whether it is crystallized. On the one hand, with the increase of annealing temperature, the crystallinity gradually increases. On the other hand, the β crystal with fewer defects makes the intermolecular force stronger and the slip less, so that the ferroelectric domain has a stronger inter-domain coupling. Even after the electric field is removed, the ferroelectric domain is more difficult to return to the original state, retaining a larger residual polarization.
[0063] (3) With the increase of annealing temperature, the content of oriented amorphous region (OAF) showed a trend of gradual increase, reaching the maximum value (0.4) when the annealing temperature reached 130℃. When the annealing temperature increased to 140℃, the content of OAF showed a trend of weakening, which was due to the fact that at higher annealing temperature, the oriented amorphous component was promoted to transform into a crystalline region with a perfect structure. It can be found that with the increase of annealing temperature, the content of crystalline region showed an increasing trend. It can also be proved that the decrease of OAF content of EFC20-A140 was due to the transformation of OAF into crystalline region. In order to more accurately determine the thickness of each component, the software was used to perform small angle x-ray diffraction analysis and correlation function analysis on poly (vinylidene fluoride-trifluoroethylene) before and after annealing. The analysis results showed that the thickness of oriented amorphous region showed a trend of gradual increase with the increase of annealing temperature and reached the maximum value (16nm) at 130℃, which indicated that the appropriate annealing temperature can effectively promote the growth of long period and oriented amorphous thickness. At the same time, it can be found that when the annealing temperature is further increased, the long period decreases and the oriented amorphous component peak disappears. This may be due to the fact that under high temperature annealing, the oriented amorphous component gradually moves to the crystal region. It can also be found that the thickness of the crystal region gradually increases with the increase of annealing temperature, which is the same trend as the increase of crystallinity with the increase of annealing temperature.
[0064] By using the above method, the poly (vinylidene fluoride-trifluoroethylene) film before and after annealing was analyzed. It can be found that with the gradual increase of annealing temperature, the crystallinity gradually increased. The crystal content of the film without annealing was only 0.28. When the annealing temperature reached 140°C, the crystal content could be increased to 0.41. Since the annealing temperature is usually higher than the Curie transition temperature and lower than the melting temperature, within this temperature range, the ferroelectric P (VDF-TrFE) transforms into a paraelectric body, the chain mobility increases, and the conformational transition and more complete crystal growth are promoted. More ferroelectric phases are helpful to further improve the piezoelectric performance.
[0065] (4) The inverse piezoelectric system of the sample is measured by piezoelectric force microscopy (PFM) to calculate the formula d 33 =(A-A0) / (V-V0) and the PFM amplitude and phase images obtained from the test to directly calculate the inverse longitudinal piezoelectric coefficient of implementation case 1 (EFC20-A130) and comparison sample 1 (EFC20-A0). It can be seen that the inverse longitudinal piezoelectric coefficient of the film after annealing at 130°C is increased from 25 picometers / volt to 42.4 picometers / volt.
[0066] In summary, the high residual polarization strength of poly(vinylidene fluoride-trifluoroethylene) combined with the stretching-induced chip orientation and defect generation produced by the electrospinning process, combined with annealing treatment, promotes the massive generation of its amorphous components in the confined chip, thereby improving the piezoelectric performance.
[0067] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0068] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a poly(vinylidene fluoride-trifluoroethylene) electrospinning piezoelectric film, characterized in that: The following steps are involved: S1, adding poly(vinylidene fluoride-trifluoroethylene) into the mixed solvent and continuously stirring to obtain a uniform electrospinning solution; S2, adding the prepared electrospinning solution into a syringe, spinning at a certain feeding speed, and spinning after adjusting the spinning parameters and environmental parameters to obtain a piezoelectric fiber membrane; S3, after completely drying the obtained piezoelectric fiber membrane in a blast oven, post-processing it, placing it in a crucible and annealing it in a muffle furnace to obtain a poly(vinylidene fluoride-trifluoroethylene) electrospun piezoelectric membrane; Wherein, the mixed solvent in step S1 is N,N-dimethylformamide and acetone.
2. The method for preparing the poly(vinylidene fluoride-trifluoroethylene) electrospinning piezoelectric film according to claim 1, characterized in that: The molar percentage of vinylidene fluoride and trifluoroethylene in the poly(vinylidene fluoride-trifluoroethylene) is 80 / 20%.
3. The method for preparing the poly(vinylidene fluoride-trifluoroethylene) electrospinning piezoelectric film according to claim 1, characterized in that: The annealing temperature is 120-140°C.
4. The method for preparing the poly(vinylidene fluoride-trifluoroethylene) electrospinning piezoelectric film according to claim 1, characterized in that: The weight average molecular weight of the poly(vinylidene fluoride-trifluoroethylene) is 450,000 g / mol.
5. The method for preparing the poly(vinylidene fluoride-trifluoroethylene) electrospinning piezoelectric film according to claim 1, characterized in that: The post-treatment process in step S3 is: placing the dried film in a 120×120 cm crucible and annealing the poly(vinylidene fluoride-trifluoroethylene) electrospun piezoelectric film using a muffle furnace.
6. The method for preparing the poly(vinylidene fluoride-trifluoroethylene) electrospinning piezoelectric film according to claim 1, characterized in that: The temperature in the forced air oven was 55°C.
7. The method for preparing the poly(vinylidene fluoride-trifluoroethylene) electrospinning piezoelectric film according to claim 1, characterized in that: In step S2, the feeding speed is 1.0 ml / h, the external electric field is 16 kV, the distance from the needle tip to the collector is 12 cm, and the drum speed is 1500 rpm: the environmental parameters are set to: 25° C. and relative humidity 40-50%.
8. The method for preparing the poly(vinylidene fluoride-trifluoroethylene) electrospinning piezoelectric film according to claim 1, characterized in that: The volume ratio of N,N-dimethylformamide to acetone in the mixed solvent is 3:2.
Citation Information
Patent Citations
Piezoelectric film, preparation method of piezoelectric film, and piezoelectric film sensor
CN110752286A
P (VDF-TrFE-CFE) nanofiber membrane with high beta crystal form as well as preparation method and application of P (VDF-TrFE-CFE) nanofiber membrane
CN116377657A
Anti-swelling PVDF (Polyvinylidene Fluoride)-based piezoelectric separation membrane based on coaxial electrospinning technology and preparation method of anti-swelling PVDF-based piezoelectric separation membrane
CN118973363A
Piezoelectric and pyroelectric film
US4557880A